2021
DOI: 10.1021/acs.jpcc.0c09666
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Multilayer MoS2 Field Effect Transistor with Unique Irradiation Resistance

Abstract: Due to their small size and low power consumption, two-dimensional (2D) MoS2 devices have emerged as attractive candidates for next-generation nanoelectronics. However, in some particular working environments, such as space applications or advanced nuclear energy systems, device degradation caused by ion irradiation is a huge challenge for practical applications. Herein, the irradiation resistance of single-layer and multilayer MoS2 field effect transistors (FETs) have been systematically studied by using 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In recent years, 2D materials-based devices, such as transistors, sensors, etc ., have been proposed as future technologies for space applications because of their low weight, small size, and low power requirements. Indeed, several groups demonstrated the radiation resistance of such 2D materials-based systems, paving the way for their use in extra-terrestrial environments. Thus, 2D materials (i) are being used for boosting/improving the performance of PSCs in terrestrial conditions and (ii) show a resistance to radiation that can be exploited for the realization of electronic devices/components used in the space environment. Consequently, we believe that the synergistic use of 2D materials within PSCs can be a promising strategy to produce efficient and reliable next-generation PV technologies .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, 2D materials-based devices, such as transistors, sensors, etc ., have been proposed as future technologies for space applications because of their low weight, small size, and low power requirements. Indeed, several groups demonstrated the radiation resistance of such 2D materials-based systems, paving the way for their use in extra-terrestrial environments. Thus, 2D materials (i) are being used for boosting/improving the performance of PSCs in terrestrial conditions and (ii) show a resistance to radiation that can be exploited for the realization of electronic devices/components used in the space environment. Consequently, we believe that the synergistic use of 2D materials within PSCs can be a promising strategy to produce efficient and reliable next-generation PV technologies .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al. [ 182 ] studied the radiation resistance of single‐ and multilayer MoS 2 FETs under another type of common irradiation source in space environment, i.e., He ions. By using 2 MeV He + irradiation it was found that single‐layer MoS 2 devices showed significant degradation with fluence of 10 11 particles cm −2 .…”
Section: Perspectives On Future Materials For Space Pvmentioning
confidence: 99%
“…The authors demonstrated that, after the irradiation with proton and electron doses of, respectively, 10 12 and 10 16 particles cm −2 (which are equivalent to those accumulated after 10 3 years of exposure at 500 km altitude), the devices did not experience any significant changes in their performances (assuming an Al shield of 1.85 nm of thickness). Recently, Zhang et al [182] studied the radiation resistance of single-and multilayer MoS 2 FETs under another type of common irradiation source in space environment, i.e., He ions. By using 2 MeV He + irradiation it was found that singlelayer MoS 2 devices showed significant degradation with fluence of 10 11 particles cm −2 .…”
Section: Perspectives On Future Materials For Space Pvmentioning
confidence: 99%
“…[ 7–10 ] Recently, TMDs have been addressed in several studies, toward the potential implementation in the nuclear energy sector and space applications, because of their intrinsically small size, lightweight, low power requirement, and distinguishable electrical/chemical properties. [ 11–13 ] One of the challenges for the sensors or electronic devices in such fields is the robustness and reliable operation under ionizing radiation such as high‐energy protons, electrons, α‐particles, X‐rays, and γ‐rays (gamma‐rays). [ 14,15 ] Several factors such as in situ healing of defects during irradiation, absence of collisional cascade, presence of grain boundary, high conductivity, nanoporosity, etc., make the 2D materials a strong candidate as a radiation‐tolerant system.…”
Section: Introductionmentioning
confidence: 99%